Investigation of sudden death caused by asymptomatic respiratory infections in infants - Ishikawa, Takaki; Tani, Naoto (Soudni lekarstvi, 2025)
Previous studies have reported that respiratory infections can cause sudden death in infants. In one report, many infants had mild respiratory infection symptoms before their sudden death. However, we have also seen many cases of sudden death in asymptomatic infants who were diagnosed with respiratory infections based on detailed postmortem examinations. However, no study has investigated the differences between symptomatic death and asymptomatic death in infants with respiratory infections. In the present study, the risk factors for sudden death in infants with asymptomatic antemortem respiratory infections were investigated using forensic autopsy cases in our laboratory. The investigation showed that deaths associated with asymptomatic respiratory infections were relatively more common in infants younger than one year, of normal birth weight, and fed exclusively with formula milk, as well as infants who had fallen asleep within one hour of their last meal. The results reconfirmed that such small daily changes, such as expression and behavior changes, should be carefully observed when managing infants, including those with no apparent health problems.
Keywords: infekce dýchací soustavy; Female; sudden unexpected death in infants (SUDI); Infant; novorozenec; Sudden Infant Death: sudden infant death syndrome (SIDS); ženské pohlaví; náhlá smrt kojenců; náhlá smrt; asymptomatické infekce; lidé; Infant, Newborn; Respiratory Tract Infections; asymptomatic sudden death; Infants; Risk Factors; Death, Sudden; Male; kojenec; Asymptomatic Infections; rizikové faktory; respiratory infection; mužské pohlaví; infants; Humans